Strengthening urban food systems through engaging with informal sector food vendors: Two models for scaling capacity sharing. Research Brief - Prain, Gordon; Alvarez, S.A.; Bertuso, A.; Sharma, G.; Kawarazuka, Nozomi; Mutua, F.; Ricarte, P. (2025)
This Research Brief documents two institutionalization and scaling models of the Vendor Business School (VBS) for strengthening urban food systems through the training and recognition of informal vendors. Drawing on contrasting experiences in Quezon City (Philippines) and Nairobi (Kenya), the brief shows that there is no single path to institutionalization: contexts with high political will allow for early collaborative models, while environments with low trust require incremental, evidence-based models focused on trust building. The capacity-sharing approach, which is gender-sensitive and co-created with authorities, demonstrates impacts on both vendor practices and institutional and regulatory changes, aligning strongly with Urban Food Systems, Systems Transformation, and Inclusive Growth.